2016
DOI: 10.1371/journal.pone.0141206
|View full text |Cite
|
Sign up to set email alerts
|

Ligation of Glycophorin A Generates Reactive Oxygen Species Leading to Decreased Red Blood Cell Function

Abstract: Acute, inflammatory conditions associated with dysregulated complement activation are characterized by significant increases in blood concentration of reactive oxygen species (ROS) and ATP. The mechanisms by which these molecules arise are not fully understood. In this study, using luminometric- and fluorescence-based methods, we show that ligation of glycophorin A (GPA) on human red blood cells (RBCs) results in a 2.1-fold, NADPH-oxidase-dependent increase in intracellular ROS that, in turn, trigger multiple … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 54 publications
0
19
0
Order By: Relevance
“…30 In targeting RBCs for delivery of therapeutics, the present findings suggest that dose-and target-dependent changes in membrane physiology, and ultimately, circulatory behavior should be carefully considered. [24][25][26][27][28][29]64 As increases in RBC rigidity can result in an override of the CD47/SIRPA interaction, 65 these factors may also play a role in RBC interactions with host defenses and immune response.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…30 In targeting RBCs for delivery of therapeutics, the present findings suggest that dose-and target-dependent changes in membrane physiology, and ultimately, circulatory behavior should be carefully considered. [24][25][26][27][28][29]64 As increases in RBC rigidity can result in an override of the CD47/SIRPA interaction, 65 these factors may also play a role in RBC interactions with host defenses and immune response.…”
Section: Discussionmentioning
confidence: 86%
“…30 Although antibodies to GPA and band 3 generally reduce membrane deformability, in early studies of the membrane deformability of antibody-coated RBCs, others observed that for some antigens, nonspherocytic antibody-sensitized RBCs could maintain normal deformability. 31 Membrane effects vary even among epitopes within the same target protein.…”
Section: Introductionmentioning
confidence: 99%
“…Whereas the function of this regulatory pathway in healthy cells remains uncertain, it should be noted that dramatically more tyrosine phosphorylation of band 3 is seen in pathologies such as sickle cell disease and β-thalassemia (32), G6PD deficiency (33), sepsis (34), and malaria parasitemia (35). Not surprisingly, most of these diseases are also characterized by an abnormal erythrocyte membrane stability/morphology, an altered rate of erythrocyte glucose metabolism, and aberrant ion transport properties (36)(37)(38)(39)(40), raising the question of whether tyrosine phosphorylation of band 3 might also contribute to the development of these diseases.…”
Section: Discussionmentioning
confidence: 99%
“…These factors include energy gains from tight adhesion to the host cell (via receptor-ligand interactions) or manipulation of the host cell cytoskeletal or membrane properties, each of which could facilitate wrapping of the merozoite. Beyond malaria invasion biology, binding of two critical red cell receptors used by the merozoite during invasion (CR1 and GPA) have been shown to transmit biophysical changes to the RBC when bound by certain ligands (16,17). To date, it has not been assessed whether parasite ligands during invasion transmit similar changes, potentially influencing invasion efficiency.…”
Section: Significancementioning
confidence: 99%